2014
DOI: 10.1038/srep03692
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic model dissects cell states in biological transition processes

Abstract: Many biological processes, including differentiation, reprogramming, and disease transformations, involve transitions of cells through distinct states. Direct, unbiased investigation of cell states and their transitions is challenging due to several factors, including limitations of single-cell assays. Here we present a stochastic model of cellular transitions that allows underlying single-cell information, including cell-state-specific parameters and rates governing transitions between states, to be estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 43 publications
(87 reference statements)
0
26
0
Order By: Relevance
“…We circumvented this problem by first determining the transition rates (which are common to the entire gene system) on a smaller subset of genes which captures the dynamical response of the whole system [3]. To select those representative genes, we clustered z-scores of log-transformed time-course data using k-means.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We circumvented this problem by first determining the transition rates (which are common to the entire gene system) on a smaller subset of genes which captures the dynamical response of the whole system [3]. To select those representative genes, we clustered z-scores of log-transformed time-course data using k-means.…”
Section: Methodsmentioning
confidence: 99%
“…The method was previously used to investigate reprogramming of mouse embryonic fibroblasts into induced pluripotent stem cells over four weeks [3]. Here we consider a different biological system, a BC model, characterized by a much shorter time scale, 32 hours.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that by using the histone deacetylase (HDAC) inhibitor Valproic acid (VPA), they could eliminate the need for oncogenes c-Myc and Klf4 (two of the four Yamanaka factors), and also found that the iPSC reprogramming efficiency was increased 100-fold over that of the four transcription factor method. Studies from Ding’s laboratory used the histone methyltransferase (HMT) inhibitor BIX-01294, to activate calcium channels in the plasma membrane, and improved the reprogramming efficiency using the four Yamanaka factors [ 15 , 16 , 17 ]. Lin et al , 2009 [ 18 ] tested several inhibitors of transforming growth factor-β (TGFβ) receptor and MAPK/ERK kinase (MEK) on primary human fibroblasts (CRL2097 or BJ) that were transduced with retrovirus carrying genes encoding the four Yamanaka factors.…”
Section: Chemically Induced Reprogramming Of Somatic Cellsmentioning
confidence: 99%
“…Cellular states are the result of differential gene expression that arises from stepwise instructive factors during development [1,2]. Alternatively, disease states or phenotypic perturbation of cellular transcriptional programs by environmental or/and genetic factors can be readily identified by gene expression changes [3,4].…”
Section: Introductionmentioning
confidence: 99%